Healthcare Worker Experiences Implementing CRE Infection Control Measures at a vSNF—A Qualitative Analysis. (October 2020) - Rynkiewich, Katharina; Makhija, Jinal; Froilan, Mary Carl; Benson, Ellen; Han, Alice; Trick, William; Weinstein, Robert; Hayden, Mary; Lin, Michael
Abstract : Background: During 2017–2019 in the Chicago region, several ventilator-capable skilled nursing facilities (vSNFs) participated in a quality improvement project to control the spread of highly prevalent carbapenem-resistant Enterobacteriaceae (CRE). With guidance from regional project coordinators and public health departments that involved education, assistance with implementation, and adherence monitoring, the facilities implemented a CRE prevention bundle that included a hand hygiene campaign that promoted alcohol-based hand rub, contact precautions (personal protective equipment with glove/gown) for care of CRE-colonized residents, and 2% chlorhexidine gluconate (CHG) wipes for routine resident bathing. We conducted a qualitative study to better understand the ways that vSNF employees engage with the implementation of such infection control measures. Methods: A PhD-candidate medical anthropologist conducted semistructured interviews with management (N = 5), nursing staff (N = 6), and certified nursing assistants (N = 6) at a vSNF in the Chicago region (Illinois) between September 2018 and November 2018. More than 11 hours of semistructured interviews were collected and transcribed. Data collection and analysis focused on identifying healthcare worker experiences during an infection control intervention. Transcriptions of the data were analyzed using thematic coding aided by MAXQDA qualitative analysis software. Results: Healthcare workers described the facility using language associated with a family environment (Table 1). Furthermore, healthcare workers demonstrated motivation to implement infection control policies (Table 2). However, healthcare workers expressed cultural and structural challenges encountered during implementation, such as their belief that some infection control measures discouraged maintenance of a home-like environment, lack of time, and understaffing. Some healthcare workers perceived that alcohol-based hand rub was ineffective over time and left unpleasant textures on the skin. Additionally, some workers did not trust the available gown and gloves used to prevent transmission. Lastly, healthcare workers typically did not prefer 2% CHG wipes over soap and water, citing residual resident postbathing smell as one indicator of CHG ineffectiveness. Conclusions: In a vSNF we found both considerable support and challenges implementing a CRE prevention bundle from the healthcare worker perspective. Healthcare workers were dedicated to recreating a home-like environment for their residents, which sometimes felt at odds with infection control interventions. Residual misconceptions (eg, alcohol-based hand rub is not effective) and negative worker perceptions (eg, permeability of contact precaution gowns and/or residue from alcohol-based hand rub) suggest that ongoing education and participation by healthcare workers in evaluating infection control products for interventions is critical. Funding: None Disclosures: None